α2,6 sialylation distinguishes a novel active state in CD4+ and CD8+ cells during acute Toxoplasma gondii infection - Sierra-Ulloa, Diego; Fernández, Jacquelina; Cacelín, María; González-Aguilar, Gloria A.; Saavedra, Rafael; Tenorio, Eda P. (Frontiers in Immunology, 2024)
Toxoplasmosis is a worldwide parasitosis that is usually asymptomatic; cell-mediated immunity, particularly T cells, is a crucial mediator of the immune response against this parasite. Membrane protein expression has been studied for a long time in T lymphocytes, providing vital information to determine functional checkpoints. However, little is known about the role of post-translational modifications in T cell function. Glycosylation plays essential roles during maturation and function; particularly, sialic acid modulation is determinant for accurate T cell regulation of processes like adhesion, cell-cell communication, and apoptosis induction. Despite its importance, the role of T cell sialylation during infection remains unclear. Herein, we aimed to evaluate whether different membrane sialylation motifs are modified in T cells during acute Toxoplasma gondii infection using different lectins. To this end, BALB/c Foxp3 EGFP mice were infected with T. gondii, and on days 3, 7, and 10 post-infection, splenocytes were obtained to analyze conventional (Foxp3 -) CD4 + and CD8 + populations by flow cytometry. Among the different lectins used for analysis, only Sambucus nigra lectin, which detects sialic acid a2,6 linkages, revealed two distinctive populations (SN Bright and SN - /Dim ) after infection. Further characterization of CD4 + and CD8 + SN -/Dim lymphocytes showed that these are highly activated cells, with a TEf/EM or TCM phenotype that produce high IFN-g levels, a previously undescribed cell state. This work demonstrates that glycan membrane analysis in T cells reveals previously overlooked functional states by evaluating only protein expression.